USULAN PENERAPAN MANUFACTURING RESOURCE PLANNING (MRP II) DI PT KSP - Hayun, Anggara; Johanda, Johanda (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
PT KSP is a fibrous food product manufacturing companies